2009 17th Euromicro International Conference on Parallel, Distributed and Network-Based Processing 2009
DOI: 10.1109/pdp.2009.53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Job and Task Placement on Parallel Scientific Applications Performance

Abstract: Abstract-this paper studies the influence that task placement may have on the performance of applications, mainly due to the relationship between communication locality and overhead. This impact is studied for torus and fat-tree topologies. A simulation-based performance study is carried out, using traces of applications and application kernels, to measure the time taken to complete one or several concurrent instances of a given workload. As the purpose of the paper is not to offer a miraculous task placement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…Regarding the quasi-contiguous allocation, we can appreciate that performance is always good, being only 30-50% higher to that obtained with purely contiguous allocation. These results confirm our expectations: a good allocation strategy can substantially reduce the execution time of a set of applications sharing a parallel computer as stated in [8]. Now we will asses the real cost of contiguity on scheduling.…”
Section: Costs and Benefits Of Contiguous Allocation Policiessupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding the quasi-contiguous allocation, we can appreciate that performance is always good, being only 30-50% higher to that obtained with purely contiguous allocation. These results confirm our expectations: a good allocation strategy can substantially reduce the execution time of a set of applications sharing a parallel computer as stated in [8]. Now we will asses the real cost of contiguity on scheduling.…”
Section: Costs and Benefits Of Contiguous Allocation Policiessupporting
confidence: 85%
“…However, our work differs from them in several important aspects. Previous research work shows that, depending on the communication pattern of the application, contiguous allocation provides remarkable performance improvements [8]. Therefore, we do not make extensive use of non-contiguity to increase system utilization; instead, we incorporate backfilling scheduling policy into the scheduler.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Practically, task placement must rely on heuristics [8]- [11]. Past work confirms the performance and cost benefits of locality-and network-aware placements on a mesh [12], [13], torus [13], [14], fat tree [14], and dragonfly [15]. In the case of a mesh, the worst-to-best ratio of application performance can reach 4× [14].…”
Section: Introductionmentioning
confidence: 80%
“…Recently, Pascual et al [4] studied the effect of job and task placement on application performance and found that maximising processor locality had a significant impact on application performance. The authors also presented a simple allocation strategy which does not consider routing containment.…”
Section: Introductionmentioning
confidence: 99%